Integration of Network Pharmacology and Experimental Validation to Explore the Pharmacological Mechanisms of Zhuanggu Busui Formula Against Osteoporosis - Zhang, Huihao; Zhou, Chengcong; Zhang, Zhiguo; Yao, Sai; Bian, Yishan; Fu, Fangda; Luo, Huan; Li, Yan; Yan, Shuxin; Ge, Yuying; Chen, Yuying; Zhan, Kunyu; et al. (Frontiers in Endocrinology, 2022)
Osteoporosis (OP) is a common skeletal disease, characterized by decreased bone formation and increased bone resorption. As a novel Chinese medicine formula, Zhuanggu Busui formula (ZGBSF) has been proved to be an effective prescription for treating OP in clinic, however, the pharmacological mechanisms underlying the beneficial effects remain obscure. In this study, we explored the pharmacological mechanisms of ZGBSF against OP via network pharmacology analysis coupled with in vivo experimental validation. The results of the network pharmacology analysis showed that a total of 86 active ingredients and 164 targets of ZGBSF associated with OP were retrieved from the corresponding databases, forming an ingredient-target-disease network. The protein-protein interaction (PPI) network manifested that 22 core targets, including Caspase-3, BCL2L1, TP53, Akt1, etc, were hub targets. Moreover, functional enrichment analyses revealed that PI3K-Akt and apoptosis signalings were significantly enriched by multiple targets and served as the targets for in vivo experimental study validation. The results of animal experiments revealed that ZGBSF not only reversed the high expression of Caspase-3, Bax, Prap, and low expression of Bcl-2 in osteoblasts of the OP mouse model but also contributed to the phosphorylation of Akt1 and expression of PI3K, thereby promoting osteogenesis and ameliorating the progression of OP. In conclusion, this study systematically and intuitively illustrated that the possible pharmacological mechanisms of ZGBSF against OP through multiple ingredients, targets, and signalings, and especially the inhibition of the apoptosis and the activation of PI3K/Akt signaling.